“Such Common Objects” – The Politics of Everyday Life in G. K. Chesterton’s and Rose Macaulay’s Thing-Essays - Daniel SCHNEIDER (E-REA)
In this article I argue that so-called light essays on apparently trivial items as they were published in periodicals of the early 20th century use the specificities of the essay genre to unveil dimensions of everyday life that are often taken for granted and thus overlooked. I will focus on two thing-essays – G. K. Chesterton’s “Lamp-Posts” (1920) and Rose Macaulay’s “Arm-Chair” (1935) – and argue that these essays help an emerging mass reader- and consumership to establish semantic coherence between themselves and the proliferating objects around them. Using Martin Heidegger’s and Bill Brown’s object-thing-distinction, I will also argue that these essays point to the relevance of everyday life and to the political issues that are sometimes manifest in everyday items. In particular, Chesterton’s and Macaulay’s thing-essays use the semantic flexibility of things to illustrate and defend their political, religious and intellectual views, touching on fields such as distributism, Catholicism and the so-called battle of the brows.